Biliary cooling during radiofrequency ablation of liver tumours close to central biliary tree: A systematic review and pooled analysis. Issue 4 (April 2021) - Feretis, M.; Wang, Y.; Zhang, B.; Liau, S.-S.
Abstract: Introduction: Biliary cooling during radiofrequency ablation (RFA) of liver tumour has been proposed as a protective measure for RFA-related biliary complications in cases whereby the RFA site is close to central biliary tree. This systematic review aims to assess the effect of biliary cooling during RFA on: 1) the development of biliary complications and 2) tumour recurrence rates at ablation site. Methodology: A systematic literature search was performed using the PubMed/EMBASE databases using PRISMA methodology (2000-2019). The initial search yielded 75 reports which were potentially suitable for inclusion. Studies reporting at least one outcome of interest were considered to be suitable for inclusion. Conference abstracts, case reports and animal studies were excluded. Data was retrieved from each study on patient demographics, tumour characteristics, method of cooling, biliary complications, local tumour recurrence and duration of follow-up. Results: The final number of studies which met the inclusion criteria was 7, involving 100 patients. There were no randomized controlled trials identified after the literature search. The mean age of the patients included was 65 years. Biliary cooling was performed with the use of a nasobiliary tube in 4 out of 7 studies, via a choledochal incision in 2 out of 7 studies and through the cystic duct in a single study. The overall biliary stricture rate was 2% and the overall tumour recurrence rate at RFA treated site was 14.5%. Conclusion: Biliary complications appear to be low after biliary cooling during RFA close to central biliary tree. More evidence is required to assess the tumour recurrence rates.